RNA Nanotechnology-Mediated Cancer Immunotherapy - Lin, Yao-Xin (Theranostics, 2020)
RNA molecules (e.g., siRNA, microRNA, and mRNA) have shown tremendous potential for immunomodulation and cancer immunotherapy. They can activate both innate and adaptive immune system responses by silencing or upregulating immune-relevant genes. In addition, mRNA-based vaccines have recently been actively pursued and tested in cancer patients, as a form of treatment. Meanwhile, various nanomaterials have been developed to enhance RNA delivery to the tumor and immune cells. In this review article, we summarize recent advances in the development of RNA-based therapeutics and their applications in cancer immunotherapy. We also highlight the variety of nanoparticle platforms that have been used for RNA delivery to elicit anti-tumor immune responses. Finally, we provide our perspectives of potential challenges and opportunities of RNA-based nanotherapeutics in clinical translation towards cancer immunotherapy.